2020
DOI: 10.1038/s41598-020-77659-x
|View full text |Cite
|
Sign up to set email alerts
|

The G protein coupled receptor CXCR4 designed by the QTY code becomes more hydrophilic and retains cell signaling activity

Abstract: G protein-coupled receptors (GPCRs) are vital for diverse biological functions, including vision, smell, and aging. They are involved in a wide range of diseases, and are among the most important targets of medicinal drugs. Tools that facilitate GPCR studies or GPCR-based technologies or therapies are thus critical to develop. Here we report using our QTY (glutamine, threonine, tyrosine) code to systematically replace 29 membrane-facing leucine, isoleucine, valine, and phenylalanine residues in the transmembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…The QTY changes hydrophobic 6TM-12TM into hydrophilic 6TM-12TM, without, however, signi cantly changing the alpha-helical molecular structures, as shown in Figure 3. Analogous reproducible experimental results reported for chemokine and cytokine receptors in our previous publications 31,32,33,34,35 . However, our experimental results showed that the structure integrity, stability, and ligand-binding activities have been retained from the water-soluble QTYvariant chemokine receptors and cytokine receptors 31,32,33,34,35 .…”
Section: Superposition Of Native Transporters and Their Water-soluble...supporting
confidence: 88%
See 2 more Smart Citations
“…The QTY changes hydrophobic 6TM-12TM into hydrophilic 6TM-12TM, without, however, signi cantly changing the alpha-helical molecular structures, as shown in Figure 3. Analogous reproducible experimental results reported for chemokine and cytokine receptors in our previous publications 31,32,33,34,35 . However, our experimental results showed that the structure integrity, stability, and ligand-binding activities have been retained from the water-soluble QTYvariant chemokine receptors and cytokine receptors 31,32,33,34,35 .…”
Section: Superposition Of Native Transporters and Their Water-soluble...supporting
confidence: 88%
“…On 15 July 2021, Google DeepMind announced the AlphaFold2, and at the same time David Baker's lab introduced RoseTTAFold as machine learning revolutionary tool for the very accurate prediction of protein structures 28,29,30 We previously applied the QTY (Glutamine, Threonine, Tyrosine) code to design several detergent-free transmembrane (TM) protein chemokine receptors and cytokine receptors for various uses using conventional computing programs to simulate several G protein-coupled receptors. Each took ~ 5 weeks to complete the simulation 33,34,35 . The expressed and puri ed water-soluble proteins exhibited predicted characteristics and retained ligand-binding activity 31,32,33,34,35 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper, Tegler et al described an early attempt in the development of the QTY code, where only 29 lipid-facing residues in CXCR4 were substituted, named as CXCR4 QTY29 . 280 The design provided a middle ground for QTY-based redesign where the receptor became more hydrophilic than the native protein, but still required detergent to stabilize in aqueous solution. It retained partial membrane-based functions.…”
Section: Qty Codementioning
confidence: 99%
“…The QTY code was initially applied to convert transmembrane (TM) α -helices of seven G protein-coupled receptors (GPCRs), namely the chemokine receptors CCR5, CCR9, CCR10, CXCR2, CXCR4, CXCR5, CXCR7 (Zhang et al ., 2018 a , 2018 b ; Qing et al ., 2019; Hao et al ., 2020; Tegler et al ., 2020; Skuhersky et al ., 2021; Tao et al ., 2022). Despite ~20–30% overall amino acid changes (46–58% transmembrane domain amino acid changes), these water-soluble QTY variant receptors still retained their overall structure, with a similar amount of α -helical content, and folded into stable proteins (Fig.…”
Section: Conversion Of a Hydrophobic α-Helix To A Hydrophilic α-Helix...mentioning
confidence: 99%